Texas blues : the rise of a contemporary sound - Govenar, Alan B., 1952- (John and Robin Dickson series in Texas music., 2008)
"Beginning in East Texas and journeying to the hot, dusty streets of Dakar, Senegal, Govenar traces the earliest roots of the music that became known as blues in the 1890s. Through a critical examination of the work of 19th and 20th century folklorists, historians, and popular writers, Govenar documents the transition from African-styled banjos and fiddles to the rudiments of blues guitar and the emergence of a distinctly Texas sound."